Behavioral effects of essential oil of Citrus aurantium L. inhalation in rats - Leite,Mariana P. (2008)
The orange essential oil (OEO) and its components obtained from Citrus aurantium L. (Rutaceae) has been attracting interest due to its sedative and relaxing actions. In the present study, rats previously exposed to OEO at the concentrations of 1.0%; 2.5% and 5.0%, w/w, by inhalation during 7 minutes in acrylic boxes were evaluated in two anxiety models: elevated plus maze (EPM) and open-field. The OEO at the concentration of 2.5% increased both the time of the animals in the open arms of the EPM and the time of active social interaction in the open-field being longer than that of the diazepam group (1.5 mg/kg i.p). In conclusion, the decrease in the level of emotionality of the animals observed in the two experimental models suggests a possible central action, which is in agreement with the phytochemical profile of the oil under study, since it showed the presence of limonene (96.24%) and mircene (2.24%), components with a well-known depressant activity on the central nervous system.